Kreativitas Guru PAI Dalam Mewujudkan Pembelajaran Bermakna (Meaningful Learning) di SMP-IT Muhammadiyah Simpang Empat - Ayu Larasati Putri Andita; Asnil Aidah Ritonga (JURNAL ASIMILASI PENDIDIKAN, 2026)
This study aims to determine the creativity of Islamic Religious Education (PAI) teachers in realizing meaningful learning at SMP-IT Muhammadiyah Simpang Empat. The research method used was qualitative, with data collection techniques through interviews, observation, and documentation. The results showed various forms of creativity in the learning process to realize meaningful learning. This creativity is evident in the use of varied media, Outing Class as contextual learning, Mabit as religious character development, and Tahfiz and Tilawah as practice-based learning. Through this creativity, students become more active, enthusiastic, and more easily understand the learning material. There are supporting and inhibiting factors in its implementation. This study provides a theoretical contribution to the development of Islamic Religious Education (PAI) learning studies, particularly regarding teacher creativity in creating meaningful and contextual learning. It also provides practical contributions for teachers and educational institutions in designing learning processes that are more creative, effective, and relevant to students' lives.